Estudo da Influência do portal concweb na aprendizagem da disciplina Estruturas de Concreto Armado - Gláucia Nolasco de Almeida Mello (2013)
This thesis presents a study on the influence of ConcWeb online virtual environment on learning process for reinforced concrete design. To acces this influence data was collected in two ways. The first one consisted of exams of student who had no contact with the environment. The second data set was composed by the same exams but for students who used ConcWeb as well as by the students' access to the virtual environment. The exams were regraded for right or wrong type answers, and then evaluated according to the Rasch model for dichotomous data. This analysis led to a measurement scale of student performance. The measurements obtained obtained durin the course of one semester were adjusted to hierarchical linear models in order to describe the students' learning trajectories in both scenarios. The results show a positive influence of ConcWeb in the students' learning process, since the access redictor variable is an important factor in the equation for the longitudinal study of the group whick used the environment.